HISTOPATHOLOGICAL DESCRIPTION OF THE NATIVE CHICKENS LUNGS WHOSE GIVEN MINYAK RAJAS - Putra, I Putu Dwi Komala; Merdana, I Made; Sri Surya Heryani, Luh Gde (Buletin Veteriner Udayana, 2022)
Minyak Rajas is a natural medicine formulated from various herbal plants containing active ingredients with pharmacological activity. This study aims to determine the effect of Minyak rajas on the lungs of male free-range chickens. The study used a completely randomized design with four treatments, namely control and three doses of Minyak rajas orally. A total of 24 male free-range chickens weighing 500-600grams were randomly divided into four treatments with six replications. As a control in the P0 group, they were fed a placebo with distilled water instead of Minyak rajas. Minyak Rajas treatment in groups P1, P2 and P3 respectively with doses of 92,3mg/kg, 184,6mg/kg and 369,2mg/kg mixed with feed for six weeks. Data analysis using the Mann-Whitney test showed that the histopathological features of the lungs found in the form of fatty degeneration, inflammatory cell infiltration, bleeding and necrosis were not significantly different (P>0.05) in all treatments. It can be concluded that the administration of Minyak Rajas has no effect on changes in the histopathological picture of the lungs of male free-range chickens. Further research can be done to increase the dose of giving Minyak Rajas orally to determine the dose limit of giving rajas oil and using more accurate parameters in identifying damage to an organ.